Protein kinase FgSch9 serves as a mediator of the target of rapamycin and high osmolarity glycerol pathways and regulates multiple stress responses and secondary metabolism in Fusarium graminearum. (26th June 2014) - Gu, Qin; Zhang, Chengqi; Yu, Fangwei; Yin, Yanni; Shim, Won‐Bo; Ma, Zhonghua
Summary: S accharomyces cerevisiae protein kinase Sch9 is one of the downstream effectors of the target of rapamycin (TOR) complex 1 and plays multiple roles in stress resistance, longevity and nutrient sensing. However, the functions of Sch9 orthologs in filamentous fungi, particularly in pathogenic species, have not been characterized to date. Here, we investigated biological and genetic functions of FgSch9 in F usarium graminearum . The FgSCH 9 deletion mutant (ΔFgSch9) was defective in aerial hyphal growth, hyphal branching and conidial germination. The mutant exhibited increased sensitivity to osmotic and oxidative stresses, cell wall‐damaging agents, and to rapamycin, while showing increased thermal tolerance. We identified FgMaf1 as one of the FgSch9‐interacting proteins that plays an important role in regulating mycotoxin biosynthesis and virulence of F . graminearum . Co‐immunoprecipitation and affinity capture‐mass spectrometry assays showed that FgSch9 also interacts with FgTor and FgHog1. More importantly, both ΔFgSch9 and FgHog1 null mutant (ΔFgHog1) exhibited increased sensitivity to osmotic and oxidative stresses. This defect was more severe in the FgSch9/FgHog1 double mutant. Taken together, we propose that FgSch9 serves as a mediator of the TOR and high osmolarity glycerol pathways, and regulates vegetative differentiation, multiple stress responses and secondary metabolism in F . graminearum .